Physical Characterization of Paper Made from Durian Peels and Corn Stalks - Nuryadin, Atin; Fitri, Muhammad Fauzan; Wati, Retno Rahma; Fadhilah, Khairunnisa Hayatul; Subagiyo, Lambang; Damayanti, Isniawana (Universitas Islam Negeri (UIN) Mataram, 2024)
The increasing demand for paper has significantly impacted the environment due to the heavy reliance on wood as a primary raw material. This study investigates the feasibility of using durian (Durio zibethinus) peels and corn (Zea mays) stalks as alternative raw materials for paper production, focusing on their physical characteristics. The paper pulp was prepared using the soda pulping method with NaOH. Various ratios of durian peels and corn stalks were mixed: 1:0 (A), 0:1 (B), 1:1 (C), 2:1 (D), and 1:2 (E). Results indicated that type D produced the thickest paper, while type A produced the thinnest. The highest grammage was observed in type E, and the lowest in type D. Type C showed the highest absorbency. The tensile and tear indexes were highest in type D and lowest in type C. Type A had the highest mass density, whereas type D had the lowest. The findings suggest that a combination of durian peel and corn stalks exhibits diverse physical properties, indicating their potential use as an alternative to conventional wood-based paper. This approach could reduce the dependency on wood and contribute to environmental conservation.